2008
DOI: 10.1123/jpah.5.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and Nonoccupational Physical Activity and the Social Determinants of Physical Activity: Results From the Health Survey for England

Abstract: Background:This article aims to examine the relative contribution of occupational activity to English adults’ meeting of government recommendations for physical activity (PA).Methods:Data were extracted from a cross-sectional survey of householders in the UK via the Health Survey for England.1 In total, 14,018 adult participants were included in the analysis. Multivariate logistic regression was used to examine the odds of achieving PA recommendations with and without including occupational activity and to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
2
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 6 publications
3
31
2
7
Order By: Relevance
“…Allender et al (2008) found that, if occupational physical activity was included, men and women in manual jobs were more likely to meet government targets for physical activity than those in non-manual jobs. In an attempt to address this we include controls for employment status and occupation in each of the models.…”
Section: Dependent Variablesmentioning
confidence: 96%
“…Allender et al (2008) found that, if occupational physical activity was included, men and women in manual jobs were more likely to meet government targets for physical activity than those in non-manual jobs. In an attempt to address this we include controls for employment status and occupation in each of the models.…”
Section: Dependent Variablesmentioning
confidence: 96%
“…Furthermore, leisure-time, work-related, and transport-related PA are often distinguished from each other. Empirical evidence suggests that socioeconomic patterns may differ for different domains of PA [15,16]. Patterns may also differ by gender, as exemplified by the finding that inequalities in overweight and obesity are larger in women [7], and by European region, as illustrated by the North to South gradient in obesity inequalities [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Transition from primary to secondary school,4 transition from high school to college or university,5 marriage,6 becoming a parent7 and retirement8 have all been suggested as important factors for change in physical activity behaviour. However, most of the existing research on physical activity patterns in older adults has been cross-sectional, and few studies have tracked individuals longitudinally from mid-life into older age.…”
Section: Introductionmentioning
confidence: 99%